Assessment of perceived fatigue and its associated factors among patient with End Stage Rental Disease and undergoing hemodialysis at King Khaled Hospital. - Elkafafi, Hanan; Deema Alshehri; Ghadeer Kabli; Afnan Mahrous (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
The literature regarding the experience of fatigue in hemodialysis patients indicates that fatigue seems to impact primarily the physical and mental domains. Physical fatigue was described by patients as a constant lack of energy, which seemed worse on dialysis days. Fatigue is negatively correlated with physical functioning, role limitations, activity levels, and mental and physical quality of life. Aim: assess level of fatigue and its associated factors among hemodialysis patients with End Stage Renal Diseases. Research design: Descriptive Correlational research design was used in this study. Setting: the current study was conduct in hemodialysis unit, Medical surgical wards, outpatient clinic in king Khaled hospital in Jeddah, Saudi Arabia. Sample: sample of 100 adult patients randomly chosen and enrolled according to the inclusive and exclusive criteria. Tool: Two tools were used for data collection in this study; first one is a personal and medical information form (PMIF) and second one is A Greek Version of Fatigue Assessment Scale (FAS) which collects information related to the perceived fatigue consisting of 10 questions. Results: majority of patients had post dialysis fatigue, (72%) of them reported moderate fatigue and (20%) of them reported severe level of fatigue with mean score (29.25±5.46). there is a relation between gender, marital status, residency, and level of education Logistic regression analysis shows that clinical and biomedical variable not associated with fatigue, Only age and gender could predict fatigue level. Conclusion: the study concluded that fatigue level vary from moderate to severe, some demographic characteristic of participate were related to fatigue, there is no association between clinical and biomedical variable and fatigue only age and gender could be a predictors for post-dialysis fatigue level. Recommendations: the study recommended that, increase nurses awareness to deal with post-dialysis fatigue symptoms by educational program. And routine screen of hemodialysis patient to detect contributing factor of fatigue early and alleviating its effects.